2010
DOI: 10.1021/jf103576r
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antitumor and Immunomodulatory Effects of the Protein PCP-3A from Mushroom Pleurotus citrinopileatus

Abstract: A nonlectin glycoprotein (PCP-3A) newly isolated from the fruit body of edible golden oyster mushroom Pleurotus citrinopileatus has been shown to be growth inhibitory against human myeloid leukemic U937 cells in a previous report. There is a well-recognized relation between antitumor activity and immunomodulation. The immunomodulatory activity of PCP-3A was therefore assessed in the present study. Human mononuclear cells (MNC) and the CD4(+) T lymphocytes isolated from them were stimulated separately with PCP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Several data reported in literature widely show that natural compounds extracted from numerous mushrooms, including some species of the genus Pleurotus, are able to inhibit tumor cell proliferation. 5,10,[16][17][18][19] According to this evidence, our results suggest that cold-water extraction allowed bioactive compounds that suppress proliferation of colon cancer cells without significant effect on proliferation of normal cells to be isolated from both P. eryngii var. ferulae and P. nebrodensis.…”
Section: A Growth Inhibition Of Hct-116 Cells By Cwe-pef and Cwe-pnmentioning
confidence: 87%
See 1 more Smart Citation
“…Several data reported in literature widely show that natural compounds extracted from numerous mushrooms, including some species of the genus Pleurotus, are able to inhibit tumor cell proliferation. 5,10,[16][17][18][19] According to this evidence, our results suggest that cold-water extraction allowed bioactive compounds that suppress proliferation of colon cancer cells without significant effect on proliferation of normal cells to be isolated from both P. eryngii var. ferulae and P. nebrodensis.…”
Section: A Growth Inhibition Of Hct-116 Cells By Cwe-pef and Cwe-pnmentioning
confidence: 87%
“…Because of the great quantity of experimental evidence collected in the past two decades, the immunomodulatory and antineoplastic properties of substances extracted from various species of edible mushrooms are now also extensively recognized at a scientific level. 3 The most promising biologically active compounds obtained from mushrooms are polysaccharides, [4][5][6][7] polysaccharide-protein complexes, 8,9 proteins, [10][11][12] and triterpenes. [13][14][15] Several published works have demonstrated that the anticancer properties of these molecules is due to their ability to en-hance immune system activity and/or act directly on cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous reports [19], we have purified a well-known glucose/mannosespecific D. lablab (DLL) lectin from the common dietary bean D. lablab of the leguminoseae family. The complete Immunomodulatory glc/man-directed DLL V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 189: [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] amino acid sequence of the lectin and its mitogenic attribute was reported long ago [14] but, despite its well-characterized and immunostimulatory properties there were only negligible reports promulgating its pharmacological implications. It is apparent that this immunomodulatory drug class has salience in oncotherapeutics, due to the notion that survival of malignant cells is dependent upon the microenvironment and evasion of the host's anti-tumour immune response [34].…”
Section: Discussionmentioning
confidence: 99%
“…In our continuing research on bioactive secondary metabolites from Pleuroutus species [12][13][14], the solid culture extract of a strain of Pleuroutus citrinopileatus Singer was also found to contain sesquiterpenes. There have been several reports on the bioactive components from P. citrinopileatus, such as a lectin with antitumor and HIV-1 reverse transcriptase inhibitory activity [15], a glycoprotein PCP-3 A with antitumor and immunomodulatory effects [16], and phenolic derivatives with antioxidant activity [17]. Separation of the EtOAc extract of P. citrinopileatus fermented on cooked rice gave one new perhydrobenzannulated 5,5spiroketal sesquiterpene (1), and six new modified bisabolene sesquiterpenes (2-7) as well as one known compound pleuroton B (8).…”
mentioning
confidence: 99%